A quenched silver-loaded cobalt-based monolithic catalyst and its preparation method and application

Through the combination of in-situ hydrothermal method and silver ion quenching liquid, the problem of the covering of the active components of the integral catalyst and insufficient mechanical strength is solved, and efficient and stable catalytic oxidation of low-carbon alkanes is achieved.

CN119281352BActive Publication Date: 2025-03-11SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411844350.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-11
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

During the preparation process of the existing monolithic catalyst, the active components are easily covered by inorganic binders, resulting in a reduced catalytic activity and insufficient mechanical strength, making it difficult to meet the practical application needs.

Method used

The precursors of cobalt and nickel are directly grown on the surface of the support by in-situ hydrothermal method. The particle size of the silver cluster is controlled by the silver ion quenching liquid, so that the silver clusters are stably anchored to the surface of active cobalt and nickel, forming an efficient cobalt-based, nickel-based and silver-based integral catalysts.

Benefits of technology

The specific surface area and catalytic properties of the catalyst are significantly improved, ensuring that the active components are not easy to fall off, and the mechanical strength of the catalyst is enhanced, achieving high-efficiency and low-cost catalytic oxidation of low-carbon alkanes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281352B_ABST
    Figure CN119281352B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalyst and catalytic technology, and relates to a catalytic oxidation technology of low-carbon alkanes in air pollution prevention and control, and specifically relates to a quenched silver-loaded cobalt-based integral catalyst and a preparation method and application thereof. The preparation method of the quenched silver-loaded cobalt-based integral catalyst comprises a cordierite carrier of a loaded precursor obtained by an in-situ hydrothermal growth method, which can generate a needle-shaped structural morphology, has relatively good mechanical strength on the one hand, and can fully expose cobalt-based and nickel-based active components on the other hand to improve the catalytic activity, and after calcining the cordierite carrier of the loaded precursor, quenching it with a silver ion quenching liquid to realize silver clusters on the surface of the cobalt-based and nickel-based active components, and forming a cobalt-based, nickel-based and silver-based integral catalyst, thereby further significantly improving the catalytic activity and the mechanical strength of the active components, thereby realizing efficient and low-cost catalytic oxidation of low-carbon alkanes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts and catalytic technology, relates to a catalytic oxidation technology of low-carbon alkanes in air pollution prevention and control, and specifically relates to a quenched silver-loaded cobalt-based integral catalyst and a preparation method and application thereof. Background Art

[0002] As a highly efficient greenhouse gas, methane has a global warming potential (GWP) far exceeding that of carbon dioxide. Its concentration in the atmosphere is low, but its impact on climate change cannot be ignored. The main sources of methane emissions include the mining and use of fossil fuels, agricultural activities (such as rice cultivation and animal husbandry), and landfills. In order to effectively control methane emissions, catalytic oxidation technology has become an important means of emission reduction due to its advantages such as high efficiency, selectivity, and ease of operation. Among them, cobalt-based spinel catalysts have attracted much attention from researchers due to their excellent catalytic performance. However, most research still focuses on the development of catalyst powders. In practical applications, monolithic catalysts are particularly important due to their wide application in air pollution control.

[0003] In the prior art, in the preparation process of the monolithic catalyst, an inorganic or organic binder and an active metal oxide are usually used to make a slurry, and the slurry is loaded on the surface of the carrier through a coating process. For example, a Chinese patent with a patent announcement number of CN111167436B involves this technology. Although this method of the prior art can fix the catalyst on the carrier, during the high-temperature sintering process, the binder may cover the active components, resulting in a decrease in the activity of the catalyst, which is difficult to meet the needs of practical applications. This challenge urgently needs to be solved through technological innovation.

[0004] In addition, the in-situ growth process provides a potential solution to the problem of active component coverage. The in-situ growth of active components on the support surface is achieved through wet chemical methods or sol-gel methods. However, unoptimized interactions between the active phase and the support, especially in the absence of proper post-treatment, may lead to poor performance. Although calcination treatment helps to remove impurities and promote crystallization, factors such as temperature gradients, stress concentration, and differences in thermal expansion coefficients during high-temperature treatment may lead to a decrease in the mechanical strength of the catalyst, limiting the practical application of in-situ growth technology.

[0005] For example, a Chinese patent application with publication number CN102151564A discloses a method for preparing a denitration monolithic catalyst and a slurry formula, which uses a catalyst, silica gel and water to prepare the monolithic catalyst by an impregnation method. However, the catalyst prepared by this method faces problems such as active component shedding and substandard performance in practical applications. These problems reveal the technical bottlenecks in the current preparation of monolithic catalysts. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a quenched silver-loaded cobalt-based integral catalyst, which has the advantages of being simple, green and environmentally friendly, and highly controllable, and the prepared integral catalyst has the advantages of high catalytic activity, active components not being easy to fall off, and good mechanical strength.

[0007] The second object of the present invention is to provide a quenched silver-loaded cobalt-based monolithic catalyst, which has the advantages of high catalytic activity, active components not being easy to fall off, and good mechanical strength.

[0008] The third object of the present invention is to provide an application of a quenched silver-loaded cobalt-based monolithic catalyst, which has the advantages of high catalytic activity and good stability.

[0009] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:

[0010] The present invention provides a method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, comprising the following steps:

[0011] S1. Carrier pretreatment: acid-washing the cordierite carrier in a mixed acid solution to obtain an acid-etched cordierite carrier;

[0012] S2. preparing a precursor solution: uniformly mixing cobalt nitrate, nickel nitrate, urea and water to obtain a precursor solution;

[0013] S3, in-situ hydrothermal growth: transferring the acid-etched cordierite carrier obtained in step S1 to a reactor containing a precursor solution, performing a hydrothermal reaction, and then washing and drying to obtain a cordierite carrier loaded with the precursor;

[0014] S4, preparing a quenching solution: dissolving polyvinyl pyrrolidone in a silver salt solution to prepare a silver ion quenching solution;

[0015] S5, calcination and quenching: calcining the cordierite carrier loaded with the precursor obtained in step S3, transferring it to the silver ion quenching liquid at the target temperature for cooling after calcination, drying it after cooling, and calcining it again to obtain the quenched silver-loaded cobalt-based monolithic catalyst.

[0016] The preparation method of a quenched silver-loaded cobalt-based monolithic catalyst of the present invention realizes the direct growth of active components on the surface of the catalyst carrier by adopting an in-situ hydrothermal method, avoids the problem of active components being covered due to the addition of an inorganic binder during the preparation process, and can significantly increase the specific surface area of ​​the monolithic catalyst and significantly improve its catalytic performance. In addition, the particle size of silver ions in the quenching liquid is controlled by the complexation of polyvinyl pyrrolidone, and then the silver is stably anchored in the form of clusters on the active cobalt and nickel surfaces through the quenching process, further greatly improving the activity of the catalyst in the oxidation reaction of light alkanes, and ensuring the high efficiency and stability of the catalyst in practical applications.

[0017] Furthermore, in step S1, the mixed acid solution is prepared from concentrated nitric acid, concentrated phosphoric acid and water, the volume ratio of the concentrated nitric acid to the concentrated phosphoric acid is (3-5):1; the volume ratio of the total volume of the concentrated nitric acid and the concentrated phosphoric acid to the water is 1:(3-5); and / or

[0018] The pickling treatment temperature is 80°C-90°C, and the pickling treatment time is 1h-2h; and / or

[0019] After the pickling treatment, ultrasonic cleaning is performed in water for 3-4 times.

[0020] Further, in step S2, the molar ratio of cobalt nitrate to nickel nitrate is (2-14):1;

[0021] The molar ratio of the total molar amount of the cobalt nitrate and the nickel nitrate to the urea is 1:(2-5); and / or

[0022] The total concentration of the cobalt nitrate and the nickel nitrate in the precursor solution is 0.4 mol / L-0.6 mol / L, and the concentration of the urea in the precursor solution is 0.8 mol / L-1.2 mol / L; and / or

[0023] The uniform mixing is achieved by stirring, and the stirring rate is 1000 rpm-2000 rpm.

[0024] Furthermore, in step S3, the hydrothermal reaction is heated to 120°C-150°C at a rate of 2°C / min-10°C / min, kept warm for 9h-24h, and then cooled naturally to room temperature.

[0025] Furthermore, in step S3, the reactor performs a hydrothermal reaction in an oven with a rotating function, and the rotation rate of the reactor is 2r / min-8r / min. In the process of the hydrothermal reaction, metal ions such as cobalt and nickel in the precursor solution are deposited on the surface of the carrier, so a concentration difference is generated on the surface of the carrier and in the precursor solution. The concentration difference can be well reduced by the effect of rotation. In addition, the precursor solution can be made more uniform by rotating the reactor, thereby achieving a relatively uniform growth of the cobalt-nickel precursor.

[0026] Furthermore, in step S4, the silver salt solution is a silver nitrate solution, the mass volume ratio of the polyvinyl pyrrolidone to the silver nitrate solution is (1-2) g:100 ml; and the molar concentration of the silver nitrate solution is 0.05M-0.2M.

[0027] Furthermore, in the step S5, the cordierite carrier loaded with the precursor obtained in step S3 is calcined at 500°C-600°C for 2h-5h, and after the calcination is completed, it is transferred to the silver ion quenching liquid at a temperature of 500°C-600°C for cooling, and after cooling, it is dried at 80°C-120°C for 10h-14h, and calcined again at 500°C-600°C for 2h-4h to obtain the quenched silver-loaded cobalt-based monolithic catalyst.

[0028] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:

[0029] The invention provides a quenched silver-loaded cobalt-based monolithic catalyst, which is prepared by the above-mentioned preparation method of the quenched silver-loaded cobalt-based monolithic catalyst.

[0030] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:

[0031] The invention provides an application of a quenched silver-loaded cobalt-based monolithic catalyst in catalytic oxidation of low-carbon alkanes.

[0032] Furthermore, the catalytic oxidation temperature of the quenched silver-loaded cobalt-based monolithic catalyst when used in the catalytic oxidation of light alkanes is 400°C-600°C.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst of the present invention comprises firstly carrying out in-situ hydrothermal growth on an acid-etched cordierite carrier to load cobalt and nickel precursors, wherein the cordierite carrier loaded with the precursor obtained by the in-situ hydrothermal growth method can generate a needle-like structural morphology, which has relatively good mechanical strength on the one hand, and can fully expose the cobalt-based and nickel-based active components on the other hand to improve the catalytic activity, and the cordierite carrier loaded with the precursor is calcined and then quenched with a silver ion quenching liquid to realize silver clusters on the surface of the cobalt-based and nickel-based active components, and form a cobalt-based, nickel-based and silver-based monolithic catalyst, thereby further significantly improving the catalytic activity and the mechanical strength of the active components, thereby realizing efficient and low-cost catalytic oxidation of low-carbon alkanes.

[0035] (2) The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst of the present invention realizes the direct growth of active components on the surface of the catalyst carrier by adopting an in-situ hydrothermal method, avoiding the problem of active components being covered due to the addition of inorganic binders during the preparation process, thereby significantly increasing the specific surface area of ​​the monolithic catalyst and significantly improving its catalytic performance. In addition, the particle size of silver ions in the quenching liquid is controlled by the complexation of polyvinyl pyrrolidone, and then the silver is stably anchored in the form of clusters on the active cobalt and nickel surfaces through the quenching process, further greatly improving the activity of the catalyst in the oxidation reaction of low-carbon alkanes, ensuring the high efficiency and stability of the catalyst in practical applications.

[0036] (3) The method for preparing a quenched silver-loaded cobalt-based integral catalyst of the present invention can achieve sufficient dispersion of silver ions by using polyvinyl pyrrolidone as a dispersant and complexing agent for silver ions. Furthermore, when the cordierite carrier of the calcined loaded precursor is quenched with a silver ion quenching liquid, silver can be uniformly clustered on the surface of the cobalt-based and nickel-based active components.

[0037] (4) The present invention provides a method for preparing a quenched silver-loaded cobalt-based integral catalyst. By quenching the cordierite carrier of the loaded precursor after calcination with a silver ion quenching liquid, on the one hand, the silver catalyst can be introduced and loaded onto the surface of the cobalt-nickel-based catalyst on the cordierite carrier to form an integral catalyst together; on the other hand, the quenching can form a silver cluster structure, which can greatly enhance the catalytic activity and the mechanical strength of the catalyst.

[0038] (5) The present invention provides a method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, which comprises in-situ growing a cobalt-nickel catalyst on a carrier, and then loading a silver cluster catalyst on the surface of the cobalt-nickel catalyst through a quenching process to form a monolithic catalyst. The preparation method has the advantages of simple process, green environmental protection, and strong controllability.

[0039] (6) The quenched silver-loaded cobalt-based monolithic catalyst of the present invention has the advantages of high catalytic activity, active components not being easy to fall off, and good mechanical strength.

[0040] (7) The use of a quenched silver-loaded cobalt-based monolithic catalyst of the present invention in the catalytic oxidation of light alkanes can achieve high-efficiency, low-cost catalytic oxidation of light alkanes and has the advantage of good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is a SEM image of a cordierite carrier loaded with a precursor (the cordierite carrier is loaded with cobalt-based and nickel-based active components) prepared by the method for preparing a quenched silver-loaded cobalt-based monolithic catalyst in Example 1 of the present invention.

[0043] Figure 2 This is a SEM image of a cordierite carrier loaded with a precursor (the cordierite carrier is loaded with a cobalt-based active component) prepared by the preparation method of a quenched silver-loaded cobalt-based monolithic catalyst in Comparative Example 1.

[0044] Figure 3 These are SEM and EDS images of the cordierite support loaded with a precursor obtained by the method for preparing a quenched silver-loaded cobalt-based monolithic catalyst in Example 1.

[0045] Figure 4 It is a graph showing the test results of CH4 catalytic combustion activity of the monolithic catalysts prepared in Example 1 and Comparative Examples 1 to 5.

[0046] Figure 5 It is the XRD diagram of the monolithic catalyst prepared in Example 1, Comparative Example 1, Comparative Example 2 and standard Co3O4.

[0047] Figure 6 This is a graph showing the long-term stability test results of the monolithic catalyst of Example 1 at 400°C.

[0048] Figure 7 This is a stability diagram of the methane catalytic combustion cycle of the integral catalyst prepared in Example 1. DETAILED DESCRIPTION

[0049] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0050] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0051] In an embodiment of the present invention, a method for preparing a quenched silver-loaded cobalt-based monolithic catalyst comprises the following steps:

[0052] S1. Carrier pretreatment: acid-washing the cordierite carrier in a mixed acid solution to obtain an acid-etched cordierite carrier;

[0053] S2. preparing a precursor solution: uniformly mixing cobalt nitrate, nickel nitrate, urea and water to obtain a precursor solution;

[0054] S3, in-situ hydrothermal growth: transferring the acid-etched cordierite carrier obtained in step S1 to a reactor containing a precursor solution, performing a hydrothermal reaction, and then washing and drying to obtain a cordierite carrier loaded with the precursor;

[0055] S4, preparing a quenching solution: dissolving polyvinyl pyrrolidone in a silver salt solution to prepare a silver ion quenching solution;

[0056] S5, calcination and quenching: calcining the cordierite carrier loaded with the precursor obtained in step S3, transferring it to the silver ion quenching liquid at the target temperature for cooling after calcination, drying it after cooling, and calcining it again to obtain the quenched silver-loaded cobalt-based monolithic catalyst.

[0057] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst in the embodiment, by adopting an in-situ hydrothermal method, realizes the direct growth of active components on the surface of the catalyst carrier, avoids the problem of active components being covered due to the addition of inorganic binders during the preparation process, and can significantly increase the specific surface area of ​​the monolithic catalyst, and significantly improve its catalytic performance. In addition, the particle size of silver ions in the quenching liquid is controlled by the complexation of polyvinyl pyrrolidone, and then the silver is stably anchored in the form of clusters on the active cobalt and nickel surfaces through the quenching process, further greatly improving the activity of the catalyst in the oxidation reaction of low-carbon alkanes, ensuring the high efficiency and stability of the catalyst in practical applications.

[0058] In some embodiments, in step S1, the mixed acid solution is prepared from concentrated nitric acid, concentrated phosphoric acid and water, the volume ratio of the concentrated nitric acid to the concentrated phosphoric acid is (3-5):1; the volume ratio of the total volume of the concentrated nitric acid and the concentrated phosphoric acid to the water is 1:(3-5); wherein the concentrated nitric acid and the concentrated phosphoric acid are both commercially available concentrated nitric acid and concentrated phosphoric acid. And / or

[0059] The pickling treatment temperature is 80°C-90°C, and the pickling treatment time is 1h-2h; and / or

[0060] After the pickling treatment, ultrasonic cleaning is performed in water for 3-4 times.

[0061] In some embodiments, in step S2, the molar ratio of cobalt nitrate to nickel nitrate is (2-14):1;

[0062] The molar ratio of the total molar amount of the cobalt nitrate and the nickel nitrate to the urea is 1:(2-5); and / or

[0063] The total concentration of the cobalt nitrate and the nickel nitrate in the precursor solution is 0.4 mol / L-0.6 mol / L, and the concentration of the urea in the precursor solution is 0.8 mol / L-1.2 mol / L; and / or

[0064] The uniform mixing is achieved by stirring, and the stirring rate is 1000 rpm-2000 rpm.

[0065] In some embodiments, in step S3, the hydrothermal reaction is heated to 120°C-150°C at a rate of 2°C / min-10°C / min, kept at that temperature for 9h-24h, and then cooled naturally to room temperature.

[0066] In some embodiments, in step S3, the reactor performs a hydrothermal reaction in an oven with a rotating function, and the rotation rate of the reactor is 2r / min-8r / min. In the process of the hydrothermal reaction, metal ions such as cobalt and nickel in the precursor solution are deposited on the surface of the carrier, so a concentration difference is generated on the surface of the carrier and in the precursor solution. The concentration difference can be well reduced by the effect of rotation. In addition, the precursor solution can be made more uniform by rotating the reactor, thereby achieving a relatively uniform growth of the cobalt-nickel precursor.

[0067] In some embodiments, in step S4, the silver salt solution is a silver nitrate solution, the mass volume ratio of the polyvinyl pyrrolidone to the silver nitrate solution is (1-2) g:100 ml; and the molar concentration of the silver nitrate solution is 0.05M-0.2M.

[0068] In some embodiments, in step S5, the cordierite carrier loaded with the precursor obtained in step S3 is calcined at 500°C-600°C for 2h-5h, and after calcination, it is transferred to the silver ion quenching liquid at a temperature of 500°C-600°C for cooling, and after cooling, it is dried at 80°C-120°C for 10h-14h, and calcined again at 500°C-600°C for 2h-4h to obtain the quenched silver-loaded cobalt-based integral catalyst.

[0069] In an embodiment of the present invention, a quenched silver-loaded cobalt-based monolithic catalyst is prepared by the above-mentioned method for preparing a quenched silver-loaded cobalt-based monolithic catalyst.

[0070] In an embodiment of the present invention, a quenched silver-loaded cobalt-based monolithic catalyst is used in the catalytic oxidation of light alkanes.

[0071] In some embodiments, the catalytic oxidation temperature of the quenched silver-loaded cobalt-based monolithic catalyst when used in the catalytic oxidation of light alkanes is 400° C.-600° C.

[0072] The following describes the invention in conjunction with specific embodiments.

[0073] Example 1

[0074] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst comprises the following steps:

[0075] S1. Carrier pretreatment: The cordierite carrier is subjected to an acid wash treatment in a mixed acid solution containing 5 mol / L nitric acid and 1 mol / L phosphoric acid at 80° C. for 1.5 h. After the acid wash treatment, the carrier is ultrasonically cleaned in water for 3 times to obtain an acid-etched cordierite carrier;

[0076] S2. Prepare a precursor solution: stir and mix cobalt nitrate, nickel nitrate, urea and water at 1500 rpm to obtain a precursor solution; in this embodiment, the molar ratio of cobalt nitrate to nickel nitrate is 8:1; the molar ratio of the total molar amount of cobalt nitrate and nickel nitrate to urea is 1:3; at this time, the total concentration of cobalt nitrate and nickel nitrate in the precursor solution is 0.5 mol / L, and the concentration of urea in the precursor solution is 1.0 mol / L;

[0077] S3, in-situ hydrothermal growth: the acid-etched cordierite carrier obtained in step S1 is transferred to a reactor containing a precursor solution, the reactor is heated to 120°C at a rate of 2°C / min in a rotating oven for hydrothermal reaction for 12 hours, then naturally cooled to room temperature, and then washed and dried to obtain a cordierite carrier loaded with the precursor; in this embodiment, the rotation rate of the reactor is 5r / min;

[0078] S4, preparing a quenching solution: dissolving polyvinyl pyrrolidone in a silver nitrate solution to prepare a silver ion quenching solution; in this embodiment, the mass volume ratio of polyvinyl pyrrolidone to the silver nitrate solution is 1.5 g:100 ml; the molar concentration of the silver nitrate solution is 0.1 M;

[0079] S5, calcination and quenching: the cordierite carrier loaded with the precursor obtained in step S3 is calcined at 500°C for 3 hours, and after calcination, it is transferred to a silver ion quenching liquid at 500°C for cooling, and after cooling, it is dried at 100°C for 12 hours, and calcined again at 500°C for 3 hours to obtain a quenched silver-loaded cobalt-based monolithic catalyst.

[0080] Among them, the present embodiment uses silver ion quenching liquid for quenching, and silver is loaded on the surface of the cobalt nickel catalyst, and the loaded silver can significantly promote the improvement of the catalytic activity of methane. In the prior art, the catalytic activity of the catalyst obtained by directly using the precursor solution to dope silver is far lower than the catalytic activity of the silver-loaded catalyst prepared by the loading method of the present invention by quenching with silver ion quenching liquid. In addition, silver nitrate is selected as the silver salt in the silver quenching liquid. During the calcination process, nitrate ions are easily decomposed, which is convenient for the loading of silver. In addition, the purpose of selecting polyvinyl pyrrolidone as an additive is to coat and disperse silver ions, thereby limiting their excessive agglomeration during the loading process, ensuring the formation of silver clusters of suitable size, and thus greatly improving the overall performance of the catalyst.

[0081] In addition, quenching with silver ion quenching liquid can form defect sites on the surface of the cobalt-nickel catalyst. The defect sites have a higher adsorption capacity for anions and are helpful for the anchoring of silver ions.

[0082] During the quenching process, the cobalt-nickel-loaded monolithic catalyst is quickly transferred to the silver ion quenching liquid at room temperature. The instantaneous change in temperature causes severe thermal stress on the catalyst surface, which in turn generates defect sites. In addition, since gaseous oxygen cannot replenish these defect sites in time, the surface is not fully repaired. At the same time, the silver ions in the silver ion quenching liquid are adsorbed onto the catalyst surface in this environment, and agglomerate through van der Waals forces and chemical adsorption interactions to gradually form silver clusters. The aggregation of silver ions not only enhances its stability on the catalyst surface, but also provides important active sites for subsequent catalytic reactions. This process not only improves the overall performance of the catalyst, but also ensures the uniform distribution and good reaction activity of the silver clusters.

[0083] Example 2

[0084] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst comprises the following steps:

[0085] S1. Carrier pretreatment: The cordierite carrier is subjected to an acid wash treatment in a mixed acid solution containing 5 mol / L nitric acid and 1 mol / L phosphoric acid at 90° C. for 1 h. After the acid wash treatment, the carrier is ultrasonically cleaned in water for 4 times to obtain an acid-etched cordierite carrier;

[0086] S2. Preparing a precursor solution: stirring and mixing cobalt nitrate, nickel nitrate, urea and water at 1000 rpm to obtain a precursor solution; in this embodiment, the molar ratio of cobalt nitrate to nickel nitrate is 2:1; the molar ratio of the total molar amount of cobalt nitrate and nickel nitrate to urea is 1:2; at this time, the total concentration of cobalt nitrate and nickel nitrate in the precursor solution is 0.4 mol / L, and the concentration of urea in the precursor solution is 0.8 mol / L;

[0087] S3, in-situ hydrothermal growth: the acid-etched cordierite carrier obtained in step S1 is transferred to a reactor containing a precursor solution, and the reactor is heated to 150°C at a rate of 10°C / min in a rotating oven for hydrothermal reaction for 9 hours, and then naturally cooled to room temperature, and then washed and dried to obtain a cordierite carrier loaded with the precursor; in this embodiment, the rotation rate of the reactor is 2r / min;

[0088] S4, preparing a quenching solution: dissolving polyvinyl pyrrolidone in a silver nitrate solution to prepare a silver ion quenching solution; in this embodiment, the mass volume ratio of polyvinyl pyrrolidone to the silver nitrate solution is 1g:100ml; the molar concentration of the silver nitrate solution is 0.05M;

[0089] S5, calcination and quenching: the cordierite carrier loaded with the precursor obtained in step S3 is calcined at 600°C for 2 hours, and after calcination, it is transferred to a silver ion quenching liquid at 600°C for cooling, and after cooling, it is dried at 80°C for 14 hours, and calcined again at 600°C for 2 hours to obtain a quenched silver-loaded cobalt-based monolithic catalyst.

[0090] Example 3

[0091] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst comprises the following steps:

[0092] S1. Carrier pretreatment: The cordierite carrier is subjected to an acid wash treatment in a mixed acid solution containing 5 mol / L nitric acid and 1 mol / L phosphoric acid at 85° C. for 2 h. After the acid wash treatment, the carrier is ultrasonically cleaned in water for 3 times to obtain an acid-etched cordierite carrier;

[0093] S2. Preparing a precursor solution: stirring and mixing cobalt nitrate, nickel nitrate, urea and water at 2000 rpm to obtain a precursor solution; in this embodiment, the molar ratio of cobalt nitrate to nickel nitrate is 14:1; the molar ratio of the total molar amount of cobalt nitrate and nickel nitrate to urea is 1:5; at this time, the total concentration of cobalt nitrate and nickel nitrate in the precursor solution is 0.6 mol / L, and the concentration of urea in the precursor solution is 1.2 mol / L;

[0094] S3, in-situ hydrothermal growth: the acid-etched cordierite carrier obtained in step S1 is transferred to a reactor containing a precursor solution, and the reactor is heated to 130°C at a rate of 6°C / min in a rotating oven for hydrothermal reaction for 24 hours, and then naturally cooled to room temperature, and then washed and dried to obtain a cordierite carrier loaded with the precursor; in this embodiment, the rotation rate of the reactor is 8r / min;

[0095] S4, preparing a quenching solution: dissolving polyvinyl pyrrolidone in a silver nitrate solution to prepare a silver ion quenching solution; in this embodiment, the mass volume ratio of polyvinyl pyrrolidone to the silver nitrate solution is 2g:100ml; the molar concentration of the silver nitrate solution is 0.2M;

[0096] S5, calcination and quenching: calcining the cordierite carrier loaded with the precursor obtained in step S3 at 550°C for 5 hours, transferring it to a silver ion quenching liquid at 550°C for cooling after calcination, drying it at 120°C for 10 hours after cooling, and calcining it again at 550°C for 4 hours to obtain a quenched silver-loaded cobalt-based monolithic catalyst.

[0097] Example 4

[0098] The invention discloses an application of a quenched silver-loaded cobalt-based monolithic catalyst in catalytic oxidation of light alkanes. Specifically, the catalytic oxidation temperature of the quenched silver-loaded cobalt-based monolithic catalyst in catalytic oxidation of light alkanes can be 400°C-600°C.

[0099] Comparative Example 1

[0100] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, the difference between this comparative example and Example 1 is that nickel nitrate is not added to the precursor solution of this comparative example, and it only consists of cobalt nitrate, urea and water. The remaining components and preparation steps are the same as those in Example 1.

[0101] Comparative Example 2

[0102] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, the difference between this comparative example and Example 1 is that manganese nitrate is used to replace nickel nitrate in the precursor solution of this comparative example. The remaining components and preparation steps are the same as those of Example 1.

[0103] Comparative Example 3

[0104] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, the difference between this comparative example and Example 1 is that nickel nitrate is not added to the precursor solution of this comparative example, which is composed of only cobalt nitrate, urea and water, and quenching with a silver ion quenching liquid is omitted, and natural cooling annealing is directly performed. The remaining components and preparation steps are the same as those in Example 1.

[0105] Comparative Example 4

[0106] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, the difference between this comparative example and Example 1 is that the quenching with a silver ion quenching liquid is omitted, and natural cooling annealing is directly performed. The remaining components and preparation steps are the same as those in Example 1.

[0107] Comparative Example 5

[0108] A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, the difference between this comparative example and Example 1 is that in the precursor solution of this comparative example, nickel nitrate is replaced by manganese nitrate. The quenching with silver ion quenching liquid is omitted, and natural cooling annealing is directly performed. The remaining components and preparation steps are the same as those in Example 1.

[0109] Structural characterization and performance testing

[0110] 1. Structural morphology characterization

[0111] 1. Morphological characterization by scanning electron microscopy

[0112] The cordierite support loaded with the precursor (the cordierite support loaded with cobalt-based and nickel-based active components) obtained in step S3 of the method for preparing a quenched silver-loaded cobalt-based monolithic catalyst in Example 1 was characterized by scanning electron microscopy (SEM). Figure 1 shown.

[0113] In addition, the cordierite carrier loaded with the precursor obtained in step S3 of the method for preparing a quenched silver-loaded cobalt-based monolithic catalyst in Example 1 was characterized by SEM and EDS (energy dispersive spectrometer analysis), as shown in FIG. Figure 3 As shown. Figure 3 , showing the microstructure of the cordierite carrier loaded with the precursor of Example 1. Figure 3 It can be seen that the section below the dotted line is a cross section of the catalyst carrier, which is composed of coarse grains, and uniformly grown nano-needle structures can be observed on the surface of the carrier. From the EDS image, it can be seen that cobalt and nickel ions are evenly distributed, proving that nickel ions are completely doped into the Co3O4 lattice. In addition, from the enlarged image of the nano-needle structure, the loaded silver clusters can be observed, and their diameter is about 10nm-15nm.

[0114] The cordierite carrier loaded with the precursor prepared by the preparation method of a quenched silver-loaded cobalt-based monolithic catalyst in Comparative Example 1 (the cordierite carrier loaded with the cobalt-based active component) was characterized by scanning electron microscopy (SEM). Figure 2 shown.

[0115] In addition, by Figure 1 It can be seen that the surface of the nickel-doped cobalt catalyst of Example 1 forms a needle-like structure. Figure 2 It can be seen that the surface of the cobalt catalyst without nickel doping cannot generate a needle-like structure morphology. The needle-like structure formed in Example 1 significantly increases the specific surface area. In addition, the strength test of the nickel-doped cobalt catalyst with the needle-like structure shows that the catalyst grown from the bottom up has good mechanical strength. Therefore, the nickel-doped cobalt catalyst prepared in Example 1 can enhance the catalytic activity of methane, and the good interaction between the surface of the nickel-doped cobalt and the silver clusters further enhances the catalytic performance of methane. These factors jointly promote the effectiveness and stability of the catalyst in the reaction.

[0116] Therefore, it can be seen that the catalytic activity of pure cobalt for methane can be further improved by doping cobalt with nickel. In addition, the cobalt-nickel loading can form a regular needle-like morphology with high mechanical strength. In addition, further loading with silver can further improve the catalytic activity of nickel-doped cobalt for methane, and quenching with a silver ion quenching liquid can ensure that silver is loaded on the surface of the cobalt-nickel catalyst in the form of clusters. Defect sites are generated by the quenching method, and "traps" are artificially constructed. Through the interaction force of atoms, the silver clusters can be anchored in the "traps" on the surface of the cobalt-nickel catalyst.

[0117] In addition, in Example 1 Doping The lattice promotes anisotropic growth of crystals by changing lattice stress, adjusting surface energy and the influence of synthesis conditions, thus forming a needle-like structure. The formation of this needle-like structure morphology is usually closely related to the balance between the growth orientation of the crystal and the surface energy.

[0118] Specifically, Has a spinel structure, in which and Located at the tetrahedral and octahedral positions respectively. lattice, due to their different ionic radii and charge distribution, may change Internal stresses and crystal distortions of the lattice induce specific crystal growth orientations. The incorporation of will induce anisotropic growth of the crystal lattice, making some crystal planes grow preferentially than other crystal planes, resulting in rapid extension of the crystal along a specific direction and eventually forming a needle-like or one-dimensional structure.

[0119] In addition, during the synthesis of nanomaterials, surface energy and energy differences among crystal planes have an important influence on the morphology. Doping changes the surface energy of each crystal plane, causing some planes to have lower energy and thus prefer to grow along these directions. Generally speaking, the lower energy planes are more exposed, while the higher energy planes tend to be suppressed. This anisotropic growth process further promotes the formation of needle-like or one-dimensional structures.

[0120] 2. Catalytic combustion activity test

[0121] The monolithic catalysts prepared in Example 1 and Comparative Examples 1 to 5 were tested for CH4 catalytic combustion activity. The test results are shown in Figure 4 shown.

[0122] In addition, the catalytic conversion rates of CH4 of the monolithic catalysts prepared in Example 1 and Comparative Examples 1 to 5 at different temperatures are shown in Table 1.

[0123] Table 1 Catalytic conversion rate of CH4 of the monolithic catalysts prepared in Example 1 and Comparative Examples 1 to 5 at different temperatures

[0124] catalyst 200℃ 300℃ 400℃ 500℃ 600℃ Example 1 0% 45% 100% 100% 100% Comparative Example 1 0% 25% 87% 100% 100% Comparative Example 2 0% 34% 92% 100% 100% Comparative Example 3 0% 21% 70% 100% 100% Comparative Example 4 0% 35% 85% 100% 100% Comparative Example 5 0% 30% 78% 100% 100%

[0125] Among them, the monolithic catalyst of Example 1 is a silver-loaded nickel-doped cobalt catalyst, the monolithic catalyst of Comparative Example 1 is a silver-loaded pure cobalt catalyst, the monolithic catalyst of Comparative Example 2 is a silver-loaded manganese-doped cobalt catalyst, and Comparative Examples 3-5 have no silver loading. Among them, the catalysts obtained in Example 1, Comparative Example 1 and Comparative Example 2 all have excellent catalytic activity, indicating that silver loading can effectively improve the catalytic activity of methane. Among them, the catalyst obtained in Example 1 has the best effect. When the conversion temperature is 400°C, a methane conversion rate of 100% can be achieved, indicating that the monolithic catalyst formed by coupling the cobalt-doped nickel catalyst with the silver cluster has the best and excellent promotion effect on methane. Compared with precious metal catalysts such as Pt and Pd, the monolithic catalyst prepared in Example 1 has the advantages of high catalytic activity and low preparation cost.

[0126] 3. Load and mechanical strength test

[0127] In industrial applications, the bonding strength between the catalytic active components and the carrier determines the service life of the catalyst. Therefore, it is necessary to test the mechanical strength of the catalytic active components in the catalyst.

[0128] The monolithic catalysts prepared in Example 1 and Comparative Examples 1 to 5 were respectively subjected to mechanical strength tests of the catalyst active components.

[0129] Among them, the test method of the mechanical strength of the active components of the catalyst includes the following steps: weigh the monolithic catalyst sample and record the mass. Add deionized water to the beaker to cover the surface of the catalyst, put the beaker into an ultrasonic cleaning machine, adjust the ultrasonic frequency to 20KHz, the power density to 0.3W / cm², and the ultrasonic time to 10min. After the ultrasonic sample is completely dried, weigh it again. The test results of the mass change of the catalyst are shown in Table 2.

[0130] Table 2 Test results of mass change of each catalyst sample

[0131] Before load (g) After load (g) Load factor (%) After ultrasound (g) Dropout rate (%) Example 1 10.54 11.64 10.48 11.37 25.17 Comparative Example 1 10.48 10.99 4.87 10.73 50.47 Comparative Example 2 10.87 11.79 8.48 11.44 38.15 Comparative Example 3 11.73 12.33 5.12 12.00 54.48 Comparative Example 4 9.87 10.97 11.12 10.71 23.87 Comparative Example 5 11.24 12.23 8.84 11.88 35.79

[0132] The mass before loading in Table 2 refers to the mass of the cordierite carrier before loading, and the mass after loading refers to the total mass of the loaded active substance and cordierite, that is, the mass of the monolithic catalyst finally obtained.

[0133] From the test results in Table 2, it can be seen that the mass change results of each catalyst sample before and after loading and after ultrasound show that the shedding rate of the active components of the catalysts prepared in Example 1 and Comparative Example 4 of the present invention is significantly lower than that of other catalysts, which indicates that the nickel-doped monolithic catalysts in Example 1 and Comparative Example 4 contribute to the improvement of the mechanical strength of the active components. In addition, there is little difference in the shedding rate between Comparative Example 1 and Comparative Example 3, between Example 1 and Comparative Example 4, and between Comparative Example 2 and Comparative Example 5, which indicates that silver loading has little effect on the improvement of the mechanical strength of the catalyst, and silver loading mainly improves the activity of the catalyst.

[0134] 4. X-ray diffraction analysis test

[0135] The monolithic catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to X-ray diffraction analysis and testing respectively. In addition, the standard Co3O4 was also subjected to X-ray diffraction analysis and testing. The test results are as follows: Figure 5 shown.

[0136] Depend on Figure 5 It can be seen that the monolithic catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 all maintain the Co3O4 structure, and no independent nickel and independent manganese phases are found in Example 1 and Comparative Example 2, indicating that the doped nickel and manganese completely enter the Co3O4 lattice. In addition, the XRD characteristics of silver clusters can be observed in Example 1, Comparative Example 1 and Comparative Example 2, proving the effective loading of silver clusters.

[0137] 5. Catalyst Cyclic Stability Test

[0138] The monolithic catalyst prepared in Example 1 was cored with a quartz sand hole opener to form a cylindrical catalyst with a diameter of 18 mm and a length of 50 mm. The catalyst was loaded into a quartz tube reactor with an inner diameter of 18 mm and a length of 400 mm, and quartz wool was filled at both ends of the catalyst bed. The reaction atmosphere consisted of 1% and 20% The composition was balanced in nitrogen, and the total flow rate was controlled at 100 mL / min. A gas chromatograph (Shimadzu 2014C) equipped with a double flame ionization detector (FID) was used to monitor the reactant concentration and the generation of catalytic oxidation products in real time. At each temperature point, after the reaction was stabilized for 60 minutes, the catalytic activity data at that temperature was recorded until the temperature was raised to 600°C. This process was repeated 3 times to evaluate the cyclic stability of the monolithic catalyst of Example 1.

[0139] Figure 6 The long-term stability test results of the monolithic catalyst of Example 1 at 400°C are shown. In the 100-hour stability test, the monolithic catalyst of Example 1 maintained good methane catalytic activity and no activity decline was found. This proves that the quenched silver-loaded cobalt-based monolithic catalyst prepared by the present invention has good long-term stability.

[0140] Figure 7 This is a graph showing the stability of the methane catalytic combustion cycle of the monolithic catalyst prepared in Example 1. Figure 7 It can be seen that in the 5 cycle tests at 400° C., the monolithic catalyst of Example 1 maintained good methane catalytic activity and no activity decrease was found. Therefore, the monolithic catalyst prepared in the present invention has excellent methane catalytic combustion cycle stability.

[0141] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a quenched silver-loaded cobalt-based monolithic catalyst, characterized in that: The following steps are involved: S1. Carrier pretreatment: acid-washing the cordierite carrier in a mixed acid solution to obtain an acid-etched cordierite carrier; The mixed acid solution is prepared from concentrated nitric acid, concentrated phosphoric acid and water; S2. Preparing a precursor solution: uniformly mixing cobalt nitrate, nickel nitrate, urea and water to obtain a precursor solution; the molar ratio of the cobalt nitrate to the nickel nitrate is (2-14):1, and the molar ratio of the total molar amount of the cobalt nitrate and the nickel nitrate to the urea is 1:(2-5); S3, in-situ hydrothermal growth: transferring the acid-etched cordierite carrier obtained in step S1 to a reactor containing a precursor solution, performing a hydrothermal reaction, and then washing and drying to obtain a cordierite carrier loaded with the precursor; S4, preparing a quenching solution: dissolving polyvinyl pyrrolidone in a silver nitrate solution to prepare a silver ion quenching solution; the mass volume ratio of the polyvinyl pyrrolidone to the silver nitrate solution is (1-2) g:100 mL; the molar concentration of the silver nitrate solution is 0.05M-0.2M; S5, calcination and quenching: calcining the cordierite carrier loaded with the precursor obtained in step S3 at 500°C-600°C for 2h-5h, transferring it to the silver ion quenching liquid at 500°C-600°C for cooling after calcination, drying it at 80°C-120°C for 10h-14h after cooling, and then calcining it at 500°C-600°C for 2h-4h to obtain the quenched silver-loaded cobalt-based monolithic catalyst.

2. The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to claim 1, characterized in that: In step S1, the volume ratio of concentrated nitric acid to concentrated phosphoric acid is (3-5):1; the volume ratio of the total volume of concentrated nitric acid and concentrated phosphoric acid to water is 1:(3-5).

3. The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to claim 1, characterized in that: In step S1, the temperature of the pickling treatment is 80°C-90°C, and the pickling treatment time is 1h-2h; after the pickling treatment, ultrasonic cleaning is performed in water for 3-4 times.

4. The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to claim 1, characterized in that: In step S2, the total concentration of the cobalt nitrate and the nickel nitrate in the precursor solution is 0.4 mol / L-0.6 mol / L, and the concentration of the urea in the precursor solution is 0.8 mol / L-1.2 mol / L.

5. The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to claim 1, characterized in that: In step S2, the uniform mixing is performed by stirring at a rate of 1000 rpm to 2000 rpm.

6. The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to claim 1, characterized in that: In step S3, the hydrothermal reaction is heated to 120°C-150°C at a rate of 2°C / min-10°C / min, kept at that temperature for 9h-24h, and then cooled naturally to room temperature.

7. The method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to claim 1, characterized in that: In step S3, the reactor performs a hydrothermal reaction in an oven with a rotating function, and the rotation rate of the reactor is 2 r / min-8 r / min.

8. A quenched silver-loaded cobalt-based monolithic catalyst, characterized in that: The catalyst is prepared by the method for preparing a quenched silver-loaded cobalt-based monolithic catalyst according to any one of claims 1 to 7.

9. Use of the quenched silver-loaded cobalt-based monolithic catalyst according to claim 8 in catalytic oxidation of light alkanes.

10. The use according to claim 9, characterized in that The catalytic oxidation temperature of the quenched silver-loaded cobalt-based integral catalyst when used in catalytic oxidation of low-carbon alkanes is 400°C-600°C.

Citation Information

Patent Citations

  • Preparation method and slurry of denitration integral type catalyst

    CN102151564A

  • Coated monolithic catalysts, their preparation methods and applications

    CN111167436B

  • Precious metal coating-carrier catalyst as well as preparation method and application thereof

    CN117899860A

  • Monolithic low-carbon alkane catalyst with in-situ grown active components as well as preparation method and application of monolithic low-carbon alkane catalyst

    CN118949998A